THE EFFECT OF REWARD TO STUDENT MOTIVATION IN KARANGANOM ELEMENTARY SCHOOL - Putri Zudhah Ferryka; Isna Rahmawati; Nela Rofisian; Sri Suwartini (El Midad, 2023)
This ex post facto quantitative study aims to determine whether delivering prizes affects the learning motivation of class II students at SDN 3 Karanganom, North Klaten. This study's variables are reward provision (independent variable) and student learning motivation (dependent variable). This study included 18 students. In this study, questionnaires and documentation were used to collect data. The data analysis technique used in this study is simple linear regression analysis. According to the study findings, there is an effect of reinforcing the learning motivation North Klaten, which is demonstrated. by the computation findings of t count > t table of 12.349 > 2.228 and a significant value of 0.000 0.05. The theory is accepted, and providing rewards can influence learning motivation by 97.4%. Keywords: Rewards, Learning Motivation, SDN 3 Karanganom